Postoperative efficacy of chondroprotectors and diacerein in dogs with osteoarthritis secondary to cranial cruciate ligament disease - Florencia Sollier Podesta; Daniela Fabiena Izquierdo Caquías (Open Veterinary Journal, 2023)
Background: Cranial cruciate ligament disease is one of the leading causes of pelvic limb claudication in canines and osteoarthritis in the stifle joint. Historically, studies have focused on surgical options to improve the stability of the stifle joint, although none of the techniques described in the literature prevents the development of osteoarthritis. Aim: This study aimed at proving the presence of osteoarthritis at the time of diagnosis of cranial cruciate ligament rupture, as well as evaluating the benefits of administering diacerein or chondroprotective coadjuvants to the extracapsular fabelo-tibial technique. Methods: Seventeen dogs aged between 2 and 8, weighing more than 25 kg, with no predilection for breed or sex, were operated on using this technique. These were divided into three groups: Diacerein (DAR), Chondroprotector (CP), and Control. The animals were treated for 90 days and controlled clinically, radiologically, and using multidimensional scales for pain and quality of life. The statistical analysis used was descriptive and through non-parametric tests. Results: All patients had some degree of osteoarthritis at the beginning of the study associated with the presence of pain. The treated groups improved the claudication scores; however, the changes were significant for the diacerein group. The pain score improved in all animals, including those in the Control group; however, the differences were significant only in the treated groups. On the other hand, no significant differences were detected in the radiological studies, so it would be convenient to perform this study over more than 90 days. Conclusion: The surgical treatment accompanied by drugs that act on the degradation of articular cartilage has better clinical results. [Open Vet J 2023; 13(3.000): 297-306]